Development of powder metallurgy route for production of novel fe-al intermetallics for high temperature applications - Mat Noor, Fazimah (2009)
FeAl based intelmetallic alloys are being proposed as engineering materials for high temperature applications due to their low density, low materials cost, low content of strategic elements and oxidation resistance. These intennetallic alloys are suitable for applications in aggressive and corrosive environments up to 900°C. However they may fail through loss of strength or gradually deteriorate through reaction with the surrounding atmosphere when exposed to temperature higher than 900°C. Therefore, the fonnation of a stable protective oxide scale or alumina on the surface is required to protect the underlying materials when exposed to high temperature. In this research, the FeAl alloys were produced by using powder metallurgy route which consisted of mechanical alloying process, cold compaction. sintering, hot compaction and surface treatment via ion implantation. The addition of reactive elements or their oxides such as Y, Y20 3 and Ce02 by mechanical alloying or ion implantation method may improve their oxidation resistance through the enhancement of the alumina scale adhesion to the underlying alloys. Characterizations by using SEM and XRD were carried out before and after each process to investigate the microstructure, phase change and fonnation of the oxide layer. Cyclic oxidation tests were perfonned at 900°C and 11 OO°C to study the oxidation behavior of these intennetallic alloys. The results showed that the FeAI intennetallic alloys were successfully produced by mechanical alloying, hot compaction and surface treatment via ion implantation. The FeAI intennetallic with 3 xl 015 ionlcm2 doses of yttrium implanted exhibited the lowest oxidation kinetics at 900°C while FeAI intennetaIIic with 1 wt% yttria and 9xl 0 15 ionlcm2 doses of yttrium implanted exhibited the lowest oxidation kinetics at 11 00°c.